Developing a shared decision support framework for aortic root surgery in Marfan syndrome. Issue 6 (5th August 2017) - Treasure, Tom; King, Annette; Hidalgo Lemp, Loreto; Golesworthy, Tal; Pepper, John; Takkenberg, Johanna JM
Abstract : Objective: The study is an early phase of development of a decision support framework for people with Marfan syndrome who are anticipating prophylactic aortic root surgery. Implications of the timing and the nature of the operation chosen were previously elicited in focus groups. In this step, we explored the range of relative values placed by individuals on the implications of decisions made about surgery. Methods: Following the principles of the Ottawa Decision Support Framework, eight questions in the general form 'How important is it to you …' were framed by a panel. Marfan people, families and specialist doctors answered online. Quantitative and qualitative analyses were performed. Results: Worldwide, 142 responses were received including 25 specialist doctors. Respondents were 55% female and 46% had previous aortic root surgery. Overall, active lifestyle was more important to males (p=0.03). Patients placed more importance than doctors on not deferring surgery (p=0.04) and on avoidance of anticoagulation in the interests of childbearing (p=0.009). Qualitative analysis showed differing but cogently reasoned values that were sometimes polarised, and mainly driven by the wish to maintain a good quality of life and active lifestyle. Conclusions: Given the cogency of these viewpoints, people anticipating root replacement surgery should have ample opportunity to express them and to have them acknowledged ahead of a consultation when they can then be fully explored in a mutually informed forum. If they differ from local medical practice, they can then be discussed in the process of reaching shared and individualised decisions.